2013
DOI: 10.1016/j.foodpol.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Food price surges and poverty in urban Colombia: New evidence from household survey data

Abstract: The present study simulates the impacts of price surges in 2006-2008 on household poverty in the main Colombian cities. It is found that the price surges increased both extreme and moderate poverty in urban areas in short and medium terms. However, the magnitude of poverty rise is not homogeneous geographically or by household typese.g., the poorest or less educated households were more badly affected than the wealthier or educated households. We suggest 'demographic targeting' or 'geographical targeting' as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The analysis of the impacts of food price issues in developing countries can be found in many pieces of literature, mostly suggesting that the increase in commodity prices will contribute to the rise in living cost and eventually poverty level. This result is consistent, be it in an agriculture net-importing country (see Timmer 2004;McCulloch 2008;Alene et al 2009;Becerril & Abdulai 2010;Rodriguez-Takeuchi & Imai 2013) or in an agriculture netexporting country (see Warr 2008;Estrades and Terra 2012;Wood et al 2012). It is mostly a consequence of poor households using most of their incomes for consumption.…”
Section: Literature Review On Food Price Issuementioning
confidence: 54%
See 3 more Smart Citations
“…The analysis of the impacts of food price issues in developing countries can be found in many pieces of literature, mostly suggesting that the increase in commodity prices will contribute to the rise in living cost and eventually poverty level. This result is consistent, be it in an agriculture net-importing country (see Timmer 2004;McCulloch 2008;Alene et al 2009;Becerril & Abdulai 2010;Rodriguez-Takeuchi & Imai 2013) or in an agriculture netexporting country (see Warr 2008;Estrades and Terra 2012;Wood et al 2012). It is mostly a consequence of poor households using most of their incomes for consumption.…”
Section: Literature Review On Food Price Issuementioning
confidence: 54%
“…(), Alom (), Wood et al . (), and Rodriguez‐Takeuchi and Imai () found that increase in food prices will contribute to the rise in the cost of living and poverty. However, the econometric approach is mostly used in the partial equilibrium model analysis focusing on the impacts on specific sector/variable, often ignoring feedbacks and indirect effects from other sectors.…”
Section: Literature Review On Food Price Issuementioning
confidence: 99%
See 2 more Smart Citations
“…As a reaction to the international commodity price spikes, the recent scientific literature has been abundant with analyses on price transmission, impacts of price shocks and policy responses to manage and cope with them (Attanasio et al, 2013;Rodriguez-Takeuchi & Imai, 2013;Baek & Koo, 2014;Baquedano & Liefert, 2014). However, little attention has been paid to the empirical analysis of the interaction between price transmission rates and the level of trade openness.…”
Section: Discussionmentioning
confidence: 99%